Impacts of water pollutants on chondrichthyans species from South America: A review - Fuentes, Sabrina Natalia (2023)
This is the first research which extensively compiles all the available scientific literature on the presence of trace metals (TMs), persistent organic pollutants (POPs), and plastic debris in Chondrichthyan species inhabiting South America (including the Atlantic and Pacific Oceans), providing an insight into Chondrichthyans as bioindicators of pollutants as well as the impacts of pollutant exposure on the organisms. Seventy-three studies were published in South America between 1986 and 2022. While 68.5% focused on TMs, 17.8% on POPs, and 9.6% on plastic debris. Brazil and Argentina were at the top in terms of the number of publications; however, there is an absence of information regarding pollutants for Chondrichthyans in Venezuela, Guyana, and French Guiana. Of the 65 Chondrichthyan species reported, 98.5% belong to the Elasmobranch group, and 1.5% from the Holocephalans. Most studies focused on Chondrichthyans of economic importance, and the most analyzed organs were the muscle and liver. There is a lack of studies on Chondrichthyan species with low economic value and critical conservation status. Due to their ecological relevance, distribution, accessibility, high trophic position, capacity to accumulate high levels of pollutants, and the number of studies published, Prionace glauca and Mustelus schmitii seem to be adequate to serve as bioindicators. For TMs, POPs, and plastic debris there is a lack of studies focusing on the pollutant levels as well as their effect on Chondrichthyans. Future research reporting TMs, POPs, and plastic debris occurrence in Chondrichthyan species are required in order to increase the scarce databases about pollutants in this group, with a clear need for further research on the responses of chondrichthyans to pollutants, as well as making inferences about the potential risks to the ecosystems and human health.